A Ponte Estaiada Octávio Frias de Oliveira na construção de sentidos para a cidade de São Paulo - Cotrim, Luciana Rossi (2013)
Beyond road functionality, Estaiada bridge Octávio Frias de Oliveira is appropriated by visuality which produces effects, from a texture of syncretic discourses interwoven through different languages: urbanistic, architectural, aesthetics, mediatic, that build the city s visibility, characterizing a polysemic way of presence which promote communicational and sociopolitical processes that signify it to São Paulo and its inhabitants and justify this choice as study object. The research refers to the way the bridge aggregates new meanings to the metropolis as it makes itself seen and lived by population, projecting the very city and its inhabitants worldwide. The main hypotesis is that the sense effects of its visibility and of interactions established with subjects in different happenings contribute to the city of São Paulo to be reinvented, sometimes as a global city, sometimes as a province. The theoretical framework is Algirdas Julien Greimas discursive semiotics, and its methodology of sense generative path in three levels: discursive, narrative and axiologic; the plastic analysis contribution from Jean-Marie Floch and Ana Claudia de Oliveira, and the sentient sense and apprehension ways analysis, as well as the regimes of interaction and of sense developed by Eric Landowski. The corpus embraces Estaiada Bridge s historical research: its building, its inauguration on May 2008, and the mediatization of different actions occurred on its roads until mid-2013. To this survey is added its presence ways apprehension, from its expression, visibility and interaction with population, disclosed in media and picked up by the researcher. The conclusion is that Estaiada Bridge Octávio Frias de Oliveira s senses go beyond emblematic discourses intentionally produced by its addressers and call upon, in the city s everyday routine, the circulation of values of (not) belonging among those who live in and out of the city, linking it to the world. These narratives and its axiologies were considered mythic in the act of semanticizing the bridge in its significant networks: as the road network of the zone where it is located and the city s, the interactions networks among subjects and the invisible networks that worldly mediatize the city of São Paulo